Firm productivity and immigrant-native earnings disparity - Olof Åslund; Cristina Bratu; Stefano Lombardi; Anna Thoresson (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
We study the role of firm productivity in explaining earnings disparities between immigrants and natives using population-wide matched employer-employee data from Sweden. We find substantial earnings returns to working in firms with higher persistent productivity, with greater gains for immigrants from non-Western countries. Moreover, the pass-through of within-firm productivity variation to earnings is stronger for immigrants in low-productive, immigrant-dense firms. But immi grant workers are underrepresented in high-productive firms and less likely to move up the productivity distribution. Thus, sorting into less productive firms decreases earnings in poor-performing immigrant groups that would gain the most from working in high-productive firms
Keywords: J15; J31; J62; 330; Firm productivity; Immigrant-native earnings gaps; Wage inequality